Activation of protein phosphatase 1 by a selective phosphatase disrupting peptide reduces sarcoplasmic reticulum Ca2+ leak in human heart failure. (7th September 2018) - Fischer, Thomas H.; Eiringhaus, Jörg; Dybkova, Nataliya; Saadatmand, Alireza; Pabel, Steffen; Weber, Silvio; Wang, Yansong; Köhn, Maja; Tirilomis, Theodor; Ljubojevic, Senka; Renner, André; Gummert, Jan; et al.
Abstract : Background: Disruption of Ca 2+ homeostasis is a key pathomechanism in heart failure. CaMKII‐dependent hyperphosphorylation of ryanodine receptors in the sarcoplasmic reticulum (SR) increases the arrhythmogenic SR Ca 2+ leak and depletes SR Ca 2+ stores. The contribution of conversely acting serine/threonine phosphatases [protein phosphatase 1 (PP1) and 2A (PP2A)] is largely unknown. Methods and results: Human myocardium from three groups of patients was investigated: (i) healthy controls (non‐failing, NF, n = 8), (ii) compensated hypertrophy (Hy, n = 16), and (iii) end‐stage heart failure (HF, n = 52). Expression of PP1 was unchanged in Hy but greater in HF compared to NF while its endogenous inhibitor‐1 (I‐1) was markedly lower expressed in both compared to NF, suggesting increased total PP1 activity. In contrast, PP2A expression was lower in Hy and HF compared to NF. Ca 2+ homeostasis was severely disturbed in HF compared to Hy signified by a higher SR Ca 2+ leak, lower systolic Ca 2+ transients as well as a decreased SR Ca 2+ load. Inhibition of PP1/PP2A by okadaic acid increased SR Ca 2+ load and systolic Ca 2+ transients but severely aggravated diastolic SR Ca 2+ leak and cellular arrhythmias in Hy. Conversely, selective activation of PP1 by a PP1‐disrupting peptide (PDP3) in HF potently reduced SR Ca 2+ leak as well as cellular arrhythmias and, importantly, did not compromise systolic Ca 2+ release and SR Ca 2+ load. Conclusion: This study is the first to functionally investigate the role of PP1/PP2A for Ca 2+ homeostasis in diseased human myocardium. Our data indicate that a modulation of phosphatase activity potently impacts Ca 2+ cycling properties. An activation of PP1 counteracts increased kinase activity in heart failure and successfully seals the arrhythmogenic SR Ca 2+ leak. It may thus represent a promising future antiarrhythmic therapeutic approach.